Judicial Interpretation of Administrative Acts Between Flawed Analogies and the Search for Criteria (TEST Antologia di Diritto Pubblico, 2026)
The essay aims to demonstrate the inadequacy of jurisprudential approaches that employ the criteria of contract interpretation (and sometimes those of the statutes) to interpret administrative acts. The paper highlights, mainly, the use of incomplete analogies by judges and the (consequent) need to identify autonomous tools for interpreting administrative acts.
Keywords: interpretation of administrative acts; interpretative criteria; incomplete analogies